Immersion Seeking Faith Understanding - APTEP and Its Theological Method - Soetomo, Greg, SJ (Archīum Ateneo, 2024)
How do we construct and organize a step-by-step of doing theology in the context of dialogue with Islam? The answer to this question is neither singular nor uniform. One of the possible paths is through immersing into a Muslim community. From such encounters, explanations are formed, then reflected upon and written systematically in the light of Catholic faith teachings. The search of this theological method is based on the evaluation and reflection on the Asia Pacific Theological Encounter Program (APTEP) conducted from June 4 to 24, 2024, in Indonesia, particularly in three cities: Jakarta, Salatiga, and Yogyakarta. This four-week program, held under the umbrella of the Jesuit Conference of Asia Pacific (JCAP), had a different focus and concentration for each week.